Evaluation Model of Supervision of Service Quality of The Final Paper in The Management Study Program, Faculty of Economics and Business, Ahmad Dahlan University - Deny Ismanto; Salamatun Asakdiyah (Westscience Press, 2023)
This research aimed to test influence between service quality, student satisfaction also interaction between service quality and student satisfaction in the building word of mouth communication. Research conducted by Department of Management, Faculty of Economics and Business, University Ahmad Dahlan. Sample categorized with sampling convenience method and purposive sampling. Data collection efforted by giving list of question to the respondent that is contains about service quality, student satisfaction and word of mouth communication. This research use Moderator Regression Analysis. In the other side, T test and F test are used to test asked hypothesis. The result of partially regression coefficient test with T test shows that service quality, student satisfaction, interaction between them influence significantly to word of mouth communication. In the other side coefficient regression test’s result shows that variables of service quality student’s satisfaction also interaction between them both influence to word of mouth communication. Variables of service quality and student’s satisfaction are able to explain word of mouth communication variable up to 78,2% and the rest is 21,8% caused by another variable that is not included in the research model